1986
DOI: 10.1212/wnl.36.4.454
|View full text |Cite
|
Sign up to set email alerts
|

Gangliosides GM1 and GD1b are antigens for IgM M-protein in a patientwith motor neuron disease

Abstract: We studied a patient with an IgM M-protein and lower motor neuron disease to identify the antigens to which the M-protein bound. Gangliosides from peripheral nerve and spinal cord were separated by high-performance thin-layer chromatography and immunostained with the patient's serum. The serum IgM immunostained two gangliosides identified as GM1 and GD1b, and immunostaining was specific for the M-protein light chain type. IgM-binding to the two gangliosides was detectable by ELISA at serum dilutions of greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1
2

Year Published

1988
1988
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(55 citation statements)
references
References 0 publications
1
51
1
2
Order By: Relevance
“…Antibody binding at these sites appears to be largely due to reactivity with GM1, rather than with other cross-reactive glycoproteins or glycolipids such as GDlb, because of the following reasons: (1) The intensity of immunostaining was proportional to the anti-GM1 antibody titers; (2) antibodies that were specific to GM1 exhibited the same pattern of reactivity; (3) the motor neurons were immunostained by CT, which is specific for GM1; and (4) anti-GM1 antibody binding to gray matter and motor neurons was specifically blocked by preincubation with CT, which does not bind to GDlb or glycoproteins. These findings are consistent with the observation that GM1 is the only common antigen found in patients with motor nerve disease and antiglycolipid antibodies [11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Antibody binding at these sites appears to be largely due to reactivity with GM1, rather than with other cross-reactive glycoproteins or glycolipids such as GDlb, because of the following reasons: (1) The intensity of immunostaining was proportional to the anti-GM1 antibody titers; (2) antibodies that were specific to GM1 exhibited the same pattern of reactivity; (3) the motor neurons were immunostained by CT, which is specific for GM1; and (4) anti-GM1 antibody binding to gray matter and motor neurons was specifically blocked by preincubation with CT, which does not bind to GDlb or glycoproteins. These findings are consistent with the observation that GM1 is the only common antigen found in patients with motor nerve disease and antiglycolipid antibodies [11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Another pos sibility is that antibodies may arise secondary to the destruction of neuronal components. Freddo et al [3] reported a patient with MND-associated IgM parapro teinemia who antibodies to GM1 and GDlb and sug gested that antibodies may play a role in the disease. Shy et al [ 14] reviewed MND with monoclonal or polyclonal paraproteinemia and showed a significnatly higher inci dence of paraproteinemia in MND than in controls and improvement in some cases by immunosuppressive ther apy.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with MND-associated IgM para proteinemia, the presence of antibodies to glycolipid has been demonstrated [3]. We searched for specific anti bodies to human spinal-cord proteins in sera from pa tients with MND and other neurological diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This is also true for analysis of the cerebrospinal fluid which, in most cases, shows a discrete increase in overall protein concentration (up to 80 mg/dl) but normal cell counts [108]. Serum electrophoresis might reveal elevated polyclonal antibody formation, while monoclonal peaks typical for IgM gammopathy are generally absent [4,109]. …”
Section: Diagnostics Of Mmnmentioning
confidence: 99%